Development of PID voltage control for DC motor using arduino - Berahim, Nawi (2014)
This project focuses on the design and implementation of PID voltage control for DC motor. DC motor is a machine that widely used due to excellence speed control for acceleration and deceleration with effective and simple torque control. The PID controller is employed to control the output voltage of three phase controlled rectifier to run a DC motor as a load. The function of this PID controller is to correct the error in order to achieve the target value of desired voltage. The modelling, control and simulation of this project has been implemented using MATLAB/Simulink Software version 2013a. The Pulse Width Modulation (PWM) signals generated from MATLAB/Simulink model will be downloaded into Arduino microcontroller. Arduino microcontroller board is an interfacing device between MATLAB/Simulink model and actual hardware. The PWM signals from Arduino will step up using gate driver and then will be sent to power MOSFET gates for triggering rectifier. The output produced from this controlled rectifier is in DC form. The open loop and closed loop simulations analyses for PID control voltage were successfully conducted. Results show that the error of voltage for closed loop is lower compared than open loop. Furthermore, hardware has been setup to verify the MATLAB/Simulink model. From here, the speed of DC motor is increased as the controlled output voltage is increased. This project contributes to the efficiency and robustness of controlling output voltage for DC motor being used in industry based on PID controller rather than using conventional method like rheostat armature control and direct on line (DOL) starter.